Early mortality in myeloma patients treated with first-generation novel agents thalidomide, lenalidomide, bortezomib at diagnosis: A pooled analysis. (October 2018) - Bringhen, Sara; Offidani, Massimo; Palmieri, Salvatore; Pisani, Francesco; Rizzi, Rita; Spada, Stefano; Evangelista, Andrea; Di Renzo, Nicola; Musto, Pellegrino; Marcatti, Magda; Vallone, Roberto; Storti, Sergio; et al.
Abstract: Introduction: Early toxic death (≤60 days of diagnosis) in elderly multiple myeloma (MM) patients is attributable to active disease, age and co-morbidities. Rate of early toxic deaths is 10% with conventional chemotherapy mainly due to infection and renal failure. Novel agents have improved MM outcome at the expense of newer toxicity. Methods: We analyzed 1146 individual patient data to assess toxic deaths during induction treatment with first-generation novel agents thalidomide, lenalidomide, bortezomib. Results: During first-line therapy, 119/1146 patients (10%) died for any cause, and 47/1146 (4%) due to toxicity, including 12/1146 (1%) early deaths. The 24-month cumulative incidence was 4.1% without any difference between bortezomib (18/503 patients, 4%) and lenalidomide (29/643patients, 5%; p = 0.31). Toxic deaths occurred in 34/1039 (3%) patients <80 years and 13/107 (12%) patients ≥80 years. Causes were cardiac events (28%), infections (26%) and vascular complications (15%). In a multivariate analysis, older age and unfavorable ISS stage increased the risk of death. Conclusion: First-generation novel agents significantly reduced toxic deaths compared to conventional chemotherapy. One third of deaths during first-line therapy were due to cumulative drug-related toxicities, thus supportive approaches and prevention strategies should be optimized. The higher mortality rate for toxicity in octogenarians confirms the need for a careful frailty assessment.